Effect of 28 days of creatine ingestion on muscle metabolism and performance of a simulated cycling road race - Hatley Holly; Sklar Josh; Dyck David J; Hickner Robert C; Byrd Priscilla (Taylor & Francis Group, 2010)
Abstract Purpose The effects of creatine supplementation on muscle metabolism and exercise performance during a simulated endurance road race was investigated. Methods Twelve adult male (27.3 ± 1.0 yr, 178.6 ± 1.4 cm, 78.0 ± 2.5 kg, 8.9 ± 1.1 %fat) endurance-trained (53.3 ± 2.0 ml* kg-1* min-1, cycling ~160 km/wk) cyclists completed a simulated road race on a cycle ergometer (Lode), consisting of a two-hour cycling bout at 60% of peak aerobic capacity (VO2peak) with three 10-second sprints performed at 110% VO2 peak every 15 minutes. Cyclists completed the 2-hr cycling bout before and after dietary creatine monohydrate or placebo supplementation (3 g/day for 28 days). Muscle biopsies were taken at rest and five minutes before the end of the two-hour ride. Results There was a 24.5 ± 10.0% increase in resting muscle total creatine and 38.4 ± 23.9% increase in muscle creatine phosphate in the creatine group (P < 0.05). Plasma glucose, blood lactate, and respiratory exchange ratio during the 2-hour ride, as well as VO2 peak, were not affected by creatine supplementation. Submaximal oxygen consumption near the end of the two-hour ride was decreased by approximately 10% by creatine supplementation (P < 0.05). Changes in plasma volume from pre- to post-supplementation were significantly greater in the creatine group (+14.0 ± 6.3%) than the placebo group (-10.4 ± 4.4%; P < 0.05) at 90 minutes of exercise. The time of the final sprint to exhaustion at the end of the 2-hour cycling bout was not affected by creatine supplementation (creatine pre, 64.4 ± 13.5s; creatine post, 88.8 ± 24.6s; placebo pre, 69.0 ± 24.8s; placebo post 92.8 ± 31.2s: creatine vs. placebo not significant). Power output for the final sprint was increased by ~33% in both groups (creatine vs. placebo not significant). Conclusions It can be concluded that although creatine supplementation may increase resting muscle total creatine, muscle creatine phosphate, and plasma volume, and may lead to a reduction in oxygen consumption during submaximal exercise, creatine supplementation does not improve sprint performance at the end of endurance cycling exercise.